Negarawan Sejati Menurut Pandangan Hamka dalam Tafsir Al-Azhar - Slamet Faozi; Rahmat Iqbal; Rifky Yulian Syah (AL-FIKRA, 2021)
AbstractThe values of struggle that have been exemplified by the nation’s predecessors are costly life lessons. Hamka's capacity as a statesman is very important so that his thoughts can be raised to future generations, because Hamka is one of the many national figures owned by Indonesia. Hamka was a man known for his strong religious understanding, and was a model of harmony between religion and state. Religion is the spirit to move and fight, and becomes the foundation and foundation in filling independence. The state is a support to establish peace in embracing religion and performing worship. Religion and state are complete units like two sides of a coin that are complementary and inseparable from each other. A true statesman according to Hamka is an individual who has a spirit of nationalism and patriotism, which conforms to the basic principles of Islam “al-amru bi al-ma’rūf wa an-nahyu ʻan al-munkar”.Keywords: statesman, nationalism, patriotismAbstrakNilai-nilai perjuangan yang telah diteladankan oleh para pendahulu bangsa merupakan pelajaran hidup yang mahal harganya. Kapasitas Hamka sebagai negarawan sangat penting untuk dimunculkan pemikirannya kepada generasi penerus bangsa, karena Hamka adalah salah satu dari sekian banyak tokoh bangsa yang dimiliki oleh Indonesia. Sosok Hamka adalah pribadi yang masyhūr dengan pemahaman keagamaannya yang kokoh, dan merupakan model keselarasan antara agama dan negara. Agama merupakan ruh untuk pergerakan dan perjuangan, dan menjadi asas serta landasan dalam mengisi kemerdekaan. Negara adalah penopang untuk mewujudkan keamanan dalam memeluk agama dan menjalankan peribadatan. Agama dan negara merupakan satu kesatuan utuh seperti dua sisi mata uang yang saling melengkapi dan tidak dapat terpisahkan satu dengan lainnya. Negarawan sejati menurut Hamka adalah individu yang berjiwa nasionalisme dan patriotisme, yang selaras dengan prinsip dasar Islam “al-amru bi al-ma’rūf wa an-nahyu ʻan al-munkar”.Kata kunci: negarawan, nasionalisme, patriotisme